2018
DOI: 10.1002/bdr2.1373
|View full text |Cite
|
Sign up to set email alerts
|

Folic acid, dietary habits, and homocysteine levels in relation to neural tube defects: A case–control study in North India

Abstract: It is suggested that plasma hyperhomocysteinemia bears negative impact on child-bearing women group, of north Indian ancestry, in modulating the risk of NTDs. Efforts should be made to enhance awareness regarding folic acid and vitamin B12 (non-vegetarian diet) supplementations alongwith proper nutritional intake among women, especially those consuming vegetarian diet to control homocysteine levels in order to reduce the risk of NTDs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 16 publications
0
7
0
3
Order By: Relevance
“…High plasma homocysteine levels has been associated with a risk for NTDs occurrence (Peker et al., 2016). Plasma homocysteine levels were found to be significantly higher in mothers of NTD offspring compared with mothers of healthy offspring (Aydin et al., 2016; Deb et al., 2018; Deshmukh et al., 2013; Gu et al., 2012; Nasri et al., 2015). In these studies, homocysteine levels were only measured in the mothers, so it is unknown whether homocysteine levels were also higher in infants with NTDs compared with healthy infants (Gu et al., 2012; Nasri et al., 2015).…”
Section: Resultsmentioning
confidence: 99%
“…High plasma homocysteine levels has been associated with a risk for NTDs occurrence (Peker et al., 2016). Plasma homocysteine levels were found to be significantly higher in mothers of NTD offspring compared with mothers of healthy offspring (Aydin et al., 2016; Deb et al., 2018; Deshmukh et al., 2013; Gu et al., 2012; Nasri et al., 2015). In these studies, homocysteine levels were only measured in the mothers, so it is unknown whether homocysteine levels were also higher in infants with NTDs compared with healthy infants (Gu et al., 2012; Nasri et al., 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Deb et al [62] observed that mean Hcy levels were elevated in cases (15.71 ± 8.35 µmol/L) of NTD births compared to controls (12.87 ± 5.95 µmol/L) but were lower among the non-vegetarians (13.55 ± 6.64 µmol/L) than the vegetarians (14.78 ± 7.93 µmol/L). Due to low intake of vitamin B12, vegetarianism increased the risk of NTDs 1.6-fold (95% CI = 1.0-2.7), while folic acid supplementation demonstrated a protective effect for conceptions (OR = 0.59; 95% CI = 0.3-0.9).…”
Section: Pregnancymentioning
confidence: 98%
“…Five hundred and ninety‐six studies were retrieved by electronic database search. Out of which 33 studies were assessed the level of homocysteine in NTD mothers (Figure 1) (Afman, Blom, Van der Put, & Van Straaten, 2003; Arbour et al, 2002; Aydin et al, 2016; Cadenas‐Benitez et al, 2014; Candito et al, 2008; Ceyhan et al, 2010; Christensen et al, 1999; Deb et al, 2018; Félix, Leistner, & Giugliani, 2004; Gaber, Farag, Soliman, El‐Bassyouni, & El‐Kamah, 2007; Godbole et al, 2011; Groenen et al, 2004; Gu, Li, Cui, & Luo, 2012; Guo et al, 2013; Gupta et al, 2018; Lacasaña et al, 2012; Lucock, Daskalakis, Lumb, Schorah, & Levene, 1998; Martín et al, 2004; Mills et al, 1995; Mobasheri, Keshtkar, & Golalipour, 2010; Paul, Sadhukhan, Munian, Bankura, & Das, 2018; Peker et al, 2016; Ratan et al, 2008; Shaw et al, 2009; Steegers‐Theunissen et al, 1994, 1995; Ubbink et al, 1999; Wang et al, 2008, 2010, 2013; Yildiz et al, 2016; Zhang et al, 2008; Zhao et al, 2006). Arbour et al (2002) reported two different populations (Cree and non‐Cree) we treated them as separate studies so finally for homocysteine we have 34 studies (2,109 cases and 3,514 controls).…”
Section: Resultsmentioning
confidence: 99%
“…Figure 1)(Afman, Blom, Van der Put, & Van Straaten, 2003;Arbour et al, 2002;Aydin et al, 2016;Cadenas-Benitez et al, 2014;Candito et al, 2008;Ceyhan et al, 2010;Christensen et al, 1999;Deb et al, 2018;Félix, Leistner, & Giugliani, 2004;Gaber, Farag, Soliman, El-Bassyouni, & El- Kamah, 2007;Godbole et al, 2011;Groenen et al, 2004;Gu, Li, Cui, & Luo, 2012;Guo et al, 2013;Gupta et al, 2018; …”
unclassified